Association of low-level environmental exposure to cadmium and lead with gout flare using a cohort study design. (October 2021) - Zhang, Hui; Li, Hailong; Green, Amanda Phipps; Wang, Ming; Yan, Fei; Li, Maichao; He, Yuwei; Sun, Wenyan; Yuan, Xuan; Lu, Jie; Sun, Mingshu; Merriman, Tony R.; et al.
Abstract: Cadmium (Cd) and lead (Pb) are toxic heavy metals with endocrine-disrupting properties. We investigated the associations of low-level environmental exposure to Cd/Pb and gout status (intercritical gout, gout flare and combined gout) in a cohort study. We measured by ICP-MS the levels of Cd and Pb in blood (Cd–B and Pb–B) and urine (Cd–U and Pb–U) from 408 participants with blood and 346 participants with urine samples recruited from a hospital gout clinic. The median levels of Cd–B and Pb–B (in μg/L) in the gout flare group were 0.87 (range 0.41–2.49) and 31.54 (25.38–41.46), respectively, and the median levels of Cd–U and Pb–U in the gout flare group were 1.05 (0.69–1.91) and 3.86 (3.49–4.44), respectively. These medians were significantly higher than those in the control or intercritical groups ( P  < 0.05). For Cd–B in tertile 2 (T2) and Cd–U in tertile 3, Cd levels were significantly associated with gout flare status compared to the reference tertile 1 (OR = 4.3, P  = 0.041 and OR = 25.1, P  = 0.002, respectively) after adjustment under Model 3. For Pb–U, the risk of gout flare status was significantly higher in T2 (OR = 51.0, P  = 0.002) compared to the T1 under Model 3. Our results show that median levels of Cd–B, Pb–B, Cd–U and Pb–U in the gout flare group were significantly higher than participants without gout or with gout but in the intercritical period. We provide evidence that the risk of gout flare status is associated with increased Cd levels, and that blood and urine levels of Cd are a risk factor for gout flare status. Graphical abstract: Image 1 Highlights: The association of environmentally low-levels of Cd and Pb with gout flare status was firstly studied. Cd and Pb levels were measured in two types of bodily sample-blood and urine. Cd and Pb levels were significantly higher in patients with gout flare than intercritical gout and healthy control. Blood and urine levels of Cd (a marker of long-term accumulation of Cd) are a risk factor for gout flare status.